2020
DOI: 10.1002/hed.26219
|View full text |Cite
|
Sign up to set email alerts
|

Rapid implementation of an evidence‐based remote triaging system for assessment of suspected referrals and patients with head and neck cancer on follow‐up after treatment during the COVID‐19 pandemic: Model for international collaboration

Abstract: Background: Outpatient telemedicine consultations are being adopted to triage patients for head and neck cancer. However, there is currently no established structure to frame this consultation.Methods: For suspected referrals with cancer, we adapted the Head and Neck Cancer Risk Calculator (HaNC-RC)-V.2, generated from 10 244 referrals with the following diagnostic efficacy metrics: 85% sensitivity, 98.6% negative predictive value, and area under the curve of 0.89. For follow-up patients, a symptom inventory g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 19 publications
0
47
0
1
Order By: Relevance
“…One such innovation is the use of a remote evidence‐based triage system (Paleri et al . 2020) to stratify patients according to likely risk of cancer. Patients with voice and swallowing symptoms, which are least likely to be attributable to a cancer diagnosis, could potentially be directed toward SLT‐led clinics (see voice services below).…”
Section: Service Delivery/clinical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…One such innovation is the use of a remote evidence‐based triage system (Paleri et al . 2020) to stratify patients according to likely risk of cancer. Patients with voice and swallowing symptoms, which are least likely to be attributable to a cancer diagnosis, could potentially be directed toward SLT‐led clinics (see voice services below).…”
Section: Service Delivery/clinical Implicationsmentioning
confidence: 99%
“…Notably, the newly proposed remote evidence‐based triage system described above (Paleri et al . 2020) could further increase referrals for SLT‐led EEL clinics. An ENT SLT‐led Two Week Wait HNC referral pathway for low risk hoarse patients pilot study demonstrated an excellent safety record for cancer screening and more efficient access to voice services (Slade and McGlashan 2019).…”
Section: Service Delivery/clinical Implicationsmentioning
confidence: 99%
“…The survey responses did not account for the number of clinics that could run simultaneously, so the estimated reduction in patient numbers is not likely to represent the full extent of the ongoing backlog. It is, therefore, important that strategies are developed to address limited space in outpatient clinics [13].…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic there has been a significant number of guidelines produced by international sources, UK governmental organisations as well as specialist bodies such as the Royal Colleges and specialist organisations [4][5][6][12][13][14][15][16][17] . These guidelines have dealt with a number of aspects including personal protective equipment, prioritisation of treatment and recovery.…”
Section: Introductionmentioning
confidence: 99%
“…These guidelines have dealt with a number of aspects including personal protective equipment, prioritisation of treatment and recovery. As well as specific aspects of Otolaryngology practice, including cancer, clinics, tracheostomy, rhinology, otology and paediatrics [4][5][6][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%